Serum Adenosine Deaminase Activity in Monitoring Disease Activity and Response to Therapy in Severe Psoriasis - Zülal Erbagci; A. Binnur Erbagci; Oya Köylüoglu; A. Almila Tuncel (Acta Medica, 2006)
Objectives: Activity of Serum Adenosine Deaminase (ADA), a main enzyme in purine degradation and considered as a marker for non-specific T cell activation, in psoriasis has been investigated in a few studies with conflicting results. Design and Methods: To evaluate the significance of serum ADA activity in psoriasis, and analyze whether ADA activity may be related to disease activity, we performed a prospective study with 38 cases of psoriasis and 24 healthy volunteers. Patients were divided into two groups as cases with local and stable lesions (Group i, n: 20) and severe cases with extensive involvement (Group ii, n: 18). Serum ADA activity was determined by modified Guisti procedure. Results: When taken into consideration of all patients -regardless of the severity of the disease- the mean serum ADA activity of psoriatics did not differ significantly from that of controls (p>0.05). However, it was higher in Group ii than in Group i and healthy controls (respectively p<0.001 and p<0.05). A significant decrease was observed also after therapy only in Group ii (p<0.001). Conclusion: Serum ADA activity may be correlated to the disease activity of severe psoriasis. We suggest that it might be a serologic marker for follow-up of in such cases. It could be used in predicting relapses before clinical findings as well as in deciding to stop or decrease systemic therapies at the right time, which have potential to cause severe systemic side effects when given for a long period. Further studies with larger case populations are required to support our findings.